Longitudinal evaluation of clinical, spectral and tissue degradation biomarkers in progression of periodontitis among cigarette and electronic cigarette smokers. (June 2021) - Akram, Zohaib; Aati, Sultan; Alrahlah, Ali; Vohra, Fahim; Fawzy, Amr
Abstract: Objectives: To longitudinally evaluate the periodontal parameters and MMP-8 and CTX (C‐terminal crosslinked telopeptide of type I collagen) levels from diseased and healthy sites from cigarette and electronic cigarette (e-cig) smokers and characterize the gingival crevicular fluid (GCF) samples using Raman spectroscopy In addition, to longitudinally determine if MMP-8 and CTX are predictive factors for attachment loss in periodontitis sites. Methods: Sixty periodontally healthy and 60 periodontitis/diseased sites from 30 e-cig and 30 cigarette smokers were monitored at baseline, 3 months, and 6-months. GCF was sampled to study the MMP-8 and CTX concentrations using enzyme-linked immunosorbent assay. Infra-red absorption spectra of GCF were acquired at all time points and processed to identify key functional groups. Results: A significantly increased attachment loss was observed at 6 months for both smokers when compared with baseline (p < 0.01). This difference was significantly high for cigarette smokers compared with e-cig users (p < 0.01). MMP-8, CTX, smoking pack-years were significantly correlated with probing depth and clinical attachment loss among both e-cig and cigarette smokers. For MMP-8 and CTX, the periodontitis sites showed a statistically significant difference between e-cig and cigarette smokers at both 3- and 6 months follow-up. From baseline to 6 months follow-up, periodontitis sites from both groups showed higher spectral band intensities with deconvulations and Raman shifts for Amide I and Amide II peaks. Conclusion: Cigarette smokers showed higher periodontal worsening than e-cig smokers. Smoking, MMP-8, CTX are prognostic factors for clinical attachment loss in cigarette and e-cig smokers. Clinical significance: Data for Raman scattering and spectral information identifying collagen degradation among e-cig and cigarette smokers have been analyzed. This type of analysis proves a robust diagnostic and prognostic tool for periodontal diseases. Smoking, MMP-8, and CTX are prognostic factors for clinical attachment loss in cigarette and e-cig smokers.